GENDER DIVERSITY AMONG THE BOARD OF COMMISSIONERS AND FIRM VALUE IN INDONESIA - Risca Dwi Jayanti; Agung Nur Probohudono; Saktiana Rizki Endiramurti (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
This research aims to empirically of the gender diversity among the board of commissioners and firm value. Specifically, the focus of this research was based on a manufacturing company located in Indonesia. The sample consists of 623 financial statements listed on the Indonesia Stock Exchange (IDX) during the 2015-2019 period. The data analyzed using multiple linear regression analysis models using EViews 10 software. In contrast to earlier research, this study incorporates empirical data from Indonesian enterprises together with a wider variety of moderating factors. In the research, a simultaneously significant effect on the value of the company is indicated by the value of R Squared of 36.3%. Based on the results of the analysis, it was concluded that the gender diversity among the board of commissioners and firm value, who were proxied by Tobin’s Q through their gender on the board of commissioners had a negative effect, where these results aren’t in line with traditional theories. Other regression analysis results, gender diversity among the board of commissioners moderating with education background had no effect on firm value, different with moderating with age factor weakens the relationship gender diversity among the board of commissioners and firm value. Our findings indicate the board of commissioners of the firm is gender diverse, and their absence has no impact on the functioning of the organization. However, due to the board of commissioners' age can be considered along with experience in carrying out the supervisory function.